Bioevaluation of agro-waste for postprandial glucose and insulin concentration in blood - Huma Umbreen; Sadia Javed; Razia Noreen; Munazzah Meraj (Journal of the Pakistan Medical Association, 2020)
Objective: The objective of the study was to evaluate the effect of apple pomace and mango peels powder supplemented cookies on postprandial glucose and insulin concentration to promote nutraceutical snacks between the meals. Methods: This single subject experimental study was conducted during Feb-Aug 2018 at Nutrition Counseling Center, GCWUF. In this study different cookies with apple pomace and mango peels powder were prepared and the most nutritive acceptable cookies were further used to determine their postprandial effect on glucose and insulin concentrations against the control cookies in female subjects. Thirty females were selected through advertisement having age 25±10 years with normal BMI (19-24.9) while the subjects having obesity, diabetes, hypertension or allergic reaction to any of content were excluded from this study. A written informed consent was obtained from all subjects. The data obtained was analyzed statistically to know the significant difference between the means. Results: The results showed that cookies supplemented with up to 15% of either mango peels or apple pomace powders were acceptable, which were further used for bio-evaluation. The human study showed that overall blood glucose and insulin concentrations were significantly lower in the treatment group specially in group with mango peels enriched cookies (103.53±2.44 mg/dL; 130.48±12.52 mg/dL) as compared to control group receiving white flour based cookies (145.00±1.15 mg/dL; 186.47±26.47 mg/dL). Conclusion: On the basis of the study it can be concluded that fruit processing waste can be used as nutraceutical agent in diet based modules and thus promoting healthy snacking which maintains postprandial Continuous...